The Concept of Epistemic Justification and the Problem of Tripartite Conditions of Knowledge in Epistemology - Ade-Ali, Funmilayo Arinola (NIU Journal of Humanities; Vol 5 No 4 (2020): KIU Journal of Humanities, Vol. 5 No. 4, December 2020, 2021)
In the recent epistemological debate over the rationality of justification of epistemic claims, there is much attempt to justify human claims to knowledge by determining the extent of the level of the role played by either reason or sense experience. This is in furtherance of widening the scope of justification of knowledge arising from the problem surrounding the rationality of knowledge right from the Socratic and Platonic period in ancient philosophy. This is given that there is a big gulf in the claims to knowledge and the evidence justifying such epistemic claims. For instance, Plato’s traditional conception of knowledge of ‘Justify True Belief’ (JTB) popularly conceived and known as a ‘tripartite condition of knowledge’; is an attempt to justify the rationality underlying true or justified epistemic claims in epistemology. On several grounds, this Platonic conception of knowledge had been questioned. For example, Edmund Gettier, an epistemologist, in his own challenge, argued that the tripartite criterion of knowledge offered by Plato is grossly inadequate and not sufficient enough to adjudge a true epistemic claim. It is on this ground that this paper examines the concept of epistemic claim to knowledge and the tripartite criteria arising from Plato’s attempt to justify the claim to knowledge in epistemology. Keywords: Epistemology, Knowledge, Tripartite, Justification, and Reason